Recovering the Divide: A Review of Strategy and Tactics in Business and Management. (27th January 2016) - Mackay, David; Zundel, Mike
Abstract : With origins in military history, strategy and tactics is a frequently used conceptual couplet in the business and management literature. This paper reviews how strategy and tactics are portrayed, identifying a dominant 'pragmatic' account of strategy as an expression of formal, planned ends achieved through the subordinate means of tactics. Pragmatic distinctions give rise to a range of well‐known problems, in particular in strategy implementation stages. We suggest that some of these problems may be avoided when the strategy–tactics relationship is conceived differently. We elaborate two alternative distinctions: a sociological framing of tactics as mechanisms of resistance to formal, controlling strategies; and a processual perspective, which sidesteps fixed distinctions between tactics and strategy, giving rise to more fluid interrelations between both modes. Based on a review of the business and management literature, we identify key examples of each trope and conclude by drawing insights for each account on the basis of these wider discussions.